Serum levels of Pentraxin 3 differ significantly at the time of blastocyst transfer depending on implantation success: a pilot study - Freis, Alexander; Horn, Kyra von; Göggl, Tamara; Hecht, Stephanie; Rösner, Sabine; Strowitzki, Thomas; Germeyer, Ariane (Archives of gynecology and obstetrics, 2018)
ObjectiveMany approaches try to identify the underlying molecular mechanisms to detect new potential biomarkers for successful artificial reproductive therapies. One factor has been described as a possible regulator of inflammation during implantation: Pentraxin 3 (PTX3), which seems to be essential for female fertility on one hand, but whose overexpression has been described in many obstetric complications based on abnormal placentation on the other hand. Therefore, we investigated if serum levels of PTX3 at the time of embryo transfer differ between women with an ongoing pregnancy compared to those without implantation.Methods/designDuring in vitro fertilization cycles of 51 patients, PTX3 levels at the time of embryo transfer were compared between patients without implantation (n = 26) and those with ongoing pregnancy (n = 25) using an enzyme-linked immunosorbent assay. Statistical analysis was performed using the Kolmogorov-Smirnov test, Fisher's exact test and Student’s t testResultsNo significant differences were found concerning possible confounders (patients age, smoking pattern, embryo quality, number of embryos transferred and prior IVF attempts). Patients without implantation presented with significantly higher serum levels of PTX3 at the time of embryo transfer compared to women who became pregnant (0.781 ± 0.074 ng/ml vs. 0.578 ± 0.055 ng/ml, p < 0.05).ConclusionsPTX3 could present as a possible biomarker for ART success. The main limitation of this pilot study is its small sample size that needs validation with a larger study population.
Gesehen am 18.07.2019